Disparitas Sistem Pidana dalam Undang-Undang Keimigrasian Indonesia Tahun 2011 - Dista Dewi Rahayu; Ridwan Arifin; Luby Lukman Zakaria (Badan Strategi Kebijakan Hukum, 2023)
The Criminal Provisions in Indonesian Immigration Law of 2011 are designed as acts of legislation for preventing transnational organized crimes in Indonesia. This law has existed for more than 10 years and has been no critical evaluation of the immigration criminal provisions. The construction of the criminal system has a non-uniform pattern of penal policy formation. This research employed the doctrinal research method with deductive reasoning that analyzed Articles on immigration criminal provisions from the perspective of Jeremy Bentham's theory of punishment analyzing the quality of criminal Articles. The results indicate that there are reactive and not pre-empting immigration criminal provisions, poor criminal provisions during immigration examinations, disparities in Judge's decisions at courts, varied patterns of punishment and sanctions, and inconsistency of criminal liability arrangements against corporations. Reconstruction of immigration criminal Articles is urged to achieve Bentham's principles and objectives of the law in sentencing. Criminal Articles should be dominated to prevent cross-border crimes during immigration clearance.